A Comparative Study of Turn-Taking in Arabic and English Conversations: Implications for Language Learners (The International Journal for Scientific Research, 2024)
Early work in conversation analysis focused primarily on English conversations. During the past 20 years, conversation analysts started to investigate informal verbal interaction within communities with a variety of linguistic and cultural backgrounds (Sidnell, 2007). Although comparative studies have examined a wide range of languages, there seems to be no emphasis on Arabic conversations. This study aims to explore whether there are differences between informal Arabic and English conversations turn-taking system. Six participants, three native Arabic speakers and three native speakers of English, took place in this study. Data were collected through audio recording; seventeen minutes for Arabic conversations and 20 minutes for the English conversation. The study revealed that there were no major differences between Arabic and English informal conversations in terms of the turn-taking system. While English speakers used more filling words such as “mm”, “yeh”, and “so” to keep the conversation going, both Arabic and English speakers aimed to minimize the gap and overlap. The findings of this study contribute to the understanding of cross-cultural interactions and offer implications for language teaching and learning.
Keywords: Conversation Analysis; Turn-Taking; Comparative Analysis; Arabic Conversation; English Conversation